My Friend Johann Baptist Metz - Moltmann, Jürgen (Theology today, 2020)
Johann Baptist Metz died on December 2, 2019. He and Jürgen Moltmann shared a theological and personal friendship marked by affection and respect. It was an honest friendship and it lasted for over fifty years. It started when two texts met: Metz’s essay “God before Us” and Moltmann’s essay “The Category of Novum in Christian Theology.” Both were published in the volume To Honor Ernst Bloch (1965). This article is a personal reminiscence.